The Development Of An Online Database For Historical Archiving Of Primary Sources - Mobo, Froilan (Future Science / FSH-PH Publications, 2021)
Historical primary sources serve as an important historical facts specially for sociologist and historian it helps them to retrieve data easily. It is very difficult to do research, data gathering specially If the data has not been stored in a cabinet or any repository properly, especially if it is being a decade or a century ago. This study will help store all the primary sources in a central database using digital technology, this approach the sociologist and historian can retrieve it easily.